Netnography Study On Covid-19 Vaccination On Dedy Corbuzier's Youtube Podcast - Destriani, Tiara Sella; Murwani, Anis Endang Sri; Indria, Indria (Universitas Dehasen Bengkulu, 2024)
This research aims to find out how the netnography study on Deddy Corbuzier's Youtube podcast in the video entitled